Ekstensifikasi Budidaya Tanaman Herbal di Desa Pace Kecamatan Silo Kabupaten Jember Menuju Desa Sentra Herbal - Iqbal Erdiansyah; Eliyatiningsih Eliyatiningsih; Dwi Nurahmanto; Vega Kartika Sari (Universitas Mataram, 2022)
Silo District is the largest ginger producing area in Jember which has great potential to be developed as an agricultural center. Several farmers in Pace Village have developed medicinal plants other than coffee plants. One of the strategies for developing medicinal plants is the preparation of appropriate cultivation technology. Efforts to realize Pace Village to become a Medicinal herbs Center Village need to be continuously supported and assisted in order to increase the quantity and quality of production. This community service activity was carried out as a follow-up to mentoring in Year 1. The activity in this second year aims to provide extensive assistance in the cultivation of medicinal plants by increasing the unit area for planting and improving cultivation production inputs to optimize and develop medicinal plant cultivation in Pace Village. The expansion of the planting area was carried out on land belonging to the village and in several yards of Gapoktan members. Improvement of production inputs through the construction of a nursery managed by the Taman Rizki Farmers Group, the addition of types of medicinal plants, and agricultural tools to support the success of medicinal herbs cultivation towards Pace Village as a Medicinal Herbs Center in Jember Regency.